Computer visualization in curve breathing analysis - Olga G. Berestneva; Gennady E. Shevelev; Ivan A. Lyzin (Известия Томского политехнического университета: Промышленная кибернетика)
The use of computer visualization methods in research not only increases the speed of information transfer and the level of its understanding, but also contributes to the development of qualities that are important for a specialist in any field, such as intuition, professional “feeling,” and imaginative thinking. Thus, the impact of interactive computer graphics has led to the emergence of a new direction in the field of artificial intelligence, called cognitive (knowledge-enhancing) computer graphics. The use of cognitive graphics allows a person to draw certain conclusions without analyzing a large amount of information. A separate direction – cognitive graphics – forms in medical research. Visualization of the patient's current condition allows for continuous monitoring of his health. The article discusses the use of computer imaging to study the characteristics of such a common disease as bronchial asthma. The purpose of the study is to analyze spirograms in different groups of patients with this disease, divided by the degree of influence of psychosocial factors on the occurrence, development and course of bronchial asthma.